Analisis Faktor-Faktor Yang Mempengaruhi Minat Perilaku Terhadap Penggunaan Sistem Informasi Akuntansi Berbasis E-Commerce (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta) - Puspaningtiyas, Ika, Dr. Fatchan Achyani, S.E, M.Si (2016)
Thisstudypurposestoexaminethefactorsthatinfluenceintention of behaviour on theusee-commercesystem.Thisresearchwasconductedat Economic and Business Faculty of Muhammadiyah Universityin Surakarta, based on convenience sampling method, number of sample used in this resear chare 98 respondent. Data wa scollected using question naire, it wa sanalyzed with multiple regression analysis. The result of study shows that attitude, subjective norm, and perceive dusefulness have effect touse behaviour in tention of e-commerce system, Even though that perceived behavior al control and perceived easy of usedid not influence tousebehaviour intention of e-commerce system. Key Word :e-commerce, subjectivenorm, perceivedus efulness, perceived behavioral control.